Capacity assessment of district health system in india on services for prevention and management of infertility - Sanjay Chauhan; Sayeed Unisa; Beena Joshi; Ragini Kulkarni; Amarjeet Singh; Thilakavathi Subramanian; Ramendra Narayan Chaudhuri; A C Baishya; Shalini Bharat; Anushree Patil; Achhelal Pasi; Dinesh Agarwal (Wolters Kluwer Medknow Publications, 2018)
Background: Infertility is a neglected service component in the public health-care system in India. Objectives: This study aims to assess the availability and practices on prevention and management services for infertility in the district health system. Methodology: A cross-sectional survey of selected health facilities and the staff from 12 district hospitals (DHs), 24 community health centers (CHCs), 48 primary health centers (PHCs), and 48 subcenters was conducted using qualitative and quantitative methods. Interviewed staff included 26 gynecologists; 91 medical officers; 91 auxiliary nurse midwife; 67 laboratory technicians; and 84 accredited social health activist workers. Results: The findings indicate that adequate staff was in place at more than 70% of health facilities, but none of the staff had received any in-service training on infertility management. Most of the DHs had basic infrastructural and diagnostic facilities. However, the majority of the CHCs and PHCs had inadequate physical and diagnostic facilities related to infertility management. Semen examination service was not available at 94% of PHCs and 79% of CHCs. Advanced laboratory services were available in <42% at DHs and 8% at CHCs. Diagnostic laparoscopy and hysteroscopy were available in 25% and 8% of DHs, respectively. Ovulation induction with clomiphene was practiced at 83% and with gonadotropins at 33% of DHs. Conclusion: The district health infrastructure in India has a potential to provide basic services for infertility. With some policy decisions, resource inputs and capacity strengthening, it is possible to provide advanced services for infertility in the district health system.